IN-SILICO ANALYSIS OF SYMBIONT BACTERIA DIVERSITY IN THE MIDGUT OF Aedes aegypti USING 16S rDNA MOLECULAR MARKERS DATABASE - Syubbanul Wathon; Aufar Finasrullah; Rike Oktarianti; Kartika Senjarini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus, which is transmitted through Aedes aegypti mosquitoes when they feed on human blood.  To effectively control the DHF vector, it is crucial to accurately characterize the symbiont bacteria associated with Ae. aegypti through an in-silico approach to identify potential targets. This study utilized in- silico analysis based on the 16S rDNA molecular marker to explore the diversity of symbiont bacteria obtained from bioinformatics databases. The analysis and visualization of bacterial diversity were conducted using the Pathosystem Resource Integration Center (PATRIC). The analysis results revealed that bacterial diversity in the midgut of Ae. aegypti, categorized as culturable and non-culturable bacteria, exhibited similar abundance patterns at the family level, albeit with varying detection rates. The most dominant taxa included the phylum Proteobacteria, class Gammaproteobacteria, order Enterobacterales, and family Enterobacteriaceae. Within the culturable bacteria category, the dominant taxa were the genus Salmonella and species Salmonella enterica, whereas the non-culturable bacteria category indicated the prevalence of the genus Escherichia and species Escherichia coli.